Isra Mi raj Mu jizat terbesar M. Mutawalli Asy Sya rawi ; penerjemah, H. Salim Basyarahil ; penyunting, Iffa Karimah - ASY SYA RAWI, M Mutawalli; Basyarahil, H. Salim; Karimah,Iffa (Gema Insani Press, 1995)
112 hlm 18 cm